2021
DOI: 10.3390/foods10102442
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Arabian Gulf Seaweeds from Kuwait as Sources of Nutritionally Important Polyunsaturated Fatty Acids (PUFAs)

Abstract: The fatty acid (FA) compositions of ten seaweeds representative of Chlorophyta, Rhodophyta, and Ochrophyta from Kuwait in the Arabian Gulf region were determined and are discussed in the context of their potential nutritional perspectives for seaweed valorization. All the seaweeds had higher saturated fatty acid (SFA) and lower monounsaturated (MUFA) and polyunsaturated fatty acid (PUFA) contents than those typical of tropical environments. Palmitic, myristic, stearic, oleic, linoleic, α-linolenic, and stearid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Kumar et al [ 59 ] observed significant individual differences in the biochemical composition of all investigated marine macroalgae. Ajayan et al [ 60 ] studied the fatty acid contents, metals and other elemental compositions of 25 macroalgal species and proved that the lipids, proteins and carbohydrate levels varied significantly among the species studied. For instance, Samanta et al [ 61 ] illustrated that the chemical composition of Agarophyton vermiculophyllum was changed by variable climatic conditions, such as temperature, pH and nutrient availability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al [ 59 ] observed significant individual differences in the biochemical composition of all investigated marine macroalgae. Ajayan et al [ 60 ] studied the fatty acid contents, metals and other elemental compositions of 25 macroalgal species and proved that the lipids, proteins and carbohydrate levels varied significantly among the species studied. For instance, Samanta et al [ 61 ] illustrated that the chemical composition of Agarophyton vermiculophyllum was changed by variable climatic conditions, such as temperature, pH and nutrient availability.…”
Section: Resultsmentioning
confidence: 99%
“…It was also described that the PUFAs content of Caulerpa is greater than those in coconut and palm oils [ 80 ]. In addition, Ajayan et al [ 60 ] stated that linolenic acid and oleic acid comprised the majority of the total fatty acids of macroalgae.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, biochemical analyses performed on Arabian Gulf Sea identify Ulva spp. as the most suitable candidates for developing low-fat food PUFA-rich nutraceuticals [53].…”
Section: Bioactive Compounds Of Seaweeds and Their Potential To Ameli...mentioning
confidence: 99%
“…(36–79%) [ 29 ]. Other authors obtained the fatty acid profile for Sargassum miyabei [ 30 ] as well as the fatty acid profile of seaweed from the Arabian Gulf region [ 31 ].…”
Section: Nutritional Composition and Bioactive Compounds In Edible Se...mentioning
confidence: 99%

Seaweeds in Food: Current Trends

Rogel-Castillo,
Latorre-Castañeda,
Muñoz-Muñoz
et al. 2023
Plants